Evaluation of a Computed Assisted Medical Intervention (CAMI) systems in scientific autopsy. (December 2017) - Grenier, F.; Voros, S.; Scolan, V.; Paysant, F.; Boutonnat, J.; Bricault, I.; Moreau-Gaudry, A.
Highlights: Build the first step of our vision to associate Computed Assisted Medical Interventions and forensic science. Show the possibility to perform mini-invasive autopsy in the autopsy room without a CT-scan in it with a radiology interventional tool. Show the limitations and the advantages of the device in this use. Show the difficulties linked to the state of the corpse. Draw conclusions on the possibilities to improve this protocol, including a per-operative tool, and continue research in this way.